Exploratory factor analysis of safety management commitment and safety administration in the context construction industries - Noor Aina Amirah, Mohd Noor; Azmi, Hassan; Nik Fadhilah, Nik Him (2020)
Exploratory Factor Analysis (EFA) was carried out to develop appropriate questionnaire items as research instruments. This study has developed and certified the instruments of safety management commitment and safety administration through the EFA study. It is applied in the context of occupational safety and health management (OSH) of construction industry. This study was divided into two constructs namely Safety Management Commitment (SMC) and Safety Administration (SA) to measure safety attitude. Safety administration construct was measured by safety programs and safety monitoring. Whereas, safety management commitment construct was measured by safety planning and safety management. This study was conducted to evaluate the contractor’s safety management attitude to the safety culture at the construction site. About 100 respondents were selected through simple random sampling to fill out the survey. Based on the reliability test, this study has set an instrument consist of eight items to develop two components for the construct of safety management commitment. While, for the construct of safety administration consist of six items for two components. This setting is based on the internal reliability value (Alpha Cronbach) for measurement of the instrument. The procedure is described in detail to carry out an EFA analysis to develop the instrument’s construct of SMC and SA. For the future, researchers can develop a study by applying instruments thoroughly in various fields of research.